The Financial Planning and its Role in Diversification and Economic Growth in Oman during the Period (1991-2021) - Qatan, Musallam; Bouabid, Dr. Anis (Migration Letters, 2023)
The aim of this study was to measure the impact of financial planning on both economic diversification and growth in Oman during the period of 1991-2021. Standard methods were used to measure the implementation rate of financial planning in its various dimensions, as well as to measure the degree of economic diversification. The study also linked the implementation indicators of the different dimensions of financial planning with the degrees of economic diversification and economic growth. The results showed that financial planning affects both the degree of diversification of gross domestic product and the degree of diversification of public revenues, but does not affect economic growth. The study found that 45.74% of the changes in the degree of diversification of gross domestic product, 26.74% of the changes in the degree of diversification of public revenues, and 38.52% of the changes in economic growth were attributed to changes in financial planning. The study recommends continuing the sound and disciplined approach to financial planning and highlighting its role as an important tool in achieving economic diversification and growth. This study contributes to clarifying the impact of integrating and combining all dimensions of financial planning in achieving important economic goals such as economic diversification and growth.